IMPLEMENTASI ANTARMUKA SINGLE PAGE APPLICATION PADA E-LEARNING UMI MENGGUNAKAN REACT.JS DAN REST API - Ibrahim Ali Abel; Ito Setiawan; Aulia Hamdi (LPPM Universitas Abdurrab, 2026)
Digital transformation in education demands the availability of e-learning platforms that are not only informative but also responsive and easy to use. This study focuses on the development of the frontend interface of the Usaha Mandiri Ibu (UMI) e-learning platform using a React.js-based Single Page Application (SPA) architecture integrated with a REST API built using Express.js on Node.js. This approach was chosen to address the limitations of conventional Multi-Page Applications (MPA), which are less efficient in page loading, and to meet the needs of the target users, namely housewives, for an intuitive and fast interface. System development was carried out using the Waterfall method, which includes the stages of analysis, design, implementation, and testing. The results show that the implementation of React.js successfully produces a modular interface that separates presentation logic from server-side business logic. Black Box testing on eight main scenarios indicates that all functions operate correctly. In addition, network performance testing using Chrome DevTools shows that page navigation is performed without a full page reload, as indicated by only a single document request (Doc request) during the initial load. These findings demonstrate that the SPA architecture improves navigation efficiency and response time, thereby supporting a more comfortable user experience.